2006
DOI: 10.1152/jn.00658.2005
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characterization of L-Type Calcium Channels and Their Contribution to Firing Behavior in Invertebrate Respiratory Neurons

Abstract: L-type calcium channel activity has been associated with a number of cytoplasmic responses, including gene transcription and activation of calcium-dependent enzymes, yet their direct contribution to the electrical activities of neurons has remained largely unexplored. Here we report the cloning and functional characterization of a molluscan L-type calcium channel homologue, LCa(v)1, and investigate its role in coordinating neuronal firing patterns. The LCav1 channel exhibits many hallmarks of vertebrate L-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(61 citation statements)
references
References 46 publications
(59 reference statements)
5
56
0
Order By: Relevance
“…As a further test for specificity of this antibody, we transfected mammalian GripTite 293 MSR cells with the Lymnaea Ca V 2 channel (Spafford et al, 2003;Spafford et al, 2004), which differs from the Aplysia Ca V 2 channel in only 2 of the 18 aa of the sequence against which the antibody was generated [SEHYNQPEWHVQFLYITE (Lymnaea) vs SEHYNQPEWFVDFLYITE (Aplysia)]. Cells were also transfected with the full-length Lymnaea Ca V 1 channel (Spafford et al, 2006). These channels were expressed in the pIRES2 bicistronic vector, where EGFP is coupled to the mRNA of LCa V 2 and LCa V 1, allowing ready visualization of transfected cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a further test for specificity of this antibody, we transfected mammalian GripTite 293 MSR cells with the Lymnaea Ca V 2 channel (Spafford et al, 2003;Spafford et al, 2004), which differs from the Aplysia Ca V 2 channel in only 2 of the 18 aa of the sequence against which the antibody was generated [SEHYNQPEWHVQFLYITE (Lymnaea) vs SEHYNQPEWFVDFLYITE (Aplysia)]. Cells were also transfected with the full-length Lymnaea Ca V 1 channel (Spafford et al, 2006). These channels were expressed in the pIRES2 bicistronic vector, where EGFP is coupled to the mRNA of LCa V 2 and LCa V 1, allowing ready visualization of transfected cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cells were transfected using the calcium phosphate method with 6.7 g of either Lymnaea stagnalis LCa V 1 channel (Spafford et al, 2006) or LCa V 2 channel (Spafford et al, 2003) ␣ 1 subunits in phosphorylated internal ribosomal entry site-enhanced green fluorescent protein (pIRES2-EGFP) vector (Clontech Laboratories, Mountain View, CA) plus 6.7 g of rat ␤ 1 subunit in pMT2 and 6.7 g of rat ␣ 2 ␦ in pMT2. Transfected cells were subsequently washed with PBS and detached using trypsin-EDTA solution (Sigma).…”
Section: Methodsmentioning
confidence: 99%
“…To study the characteristics of the LCa v 2 calcium channel, the wildtype LCa v 2 gene was cloned into pIRES2-EGFP vector from a previously modified LCa v 2 construct, dubbed 5ЈRatCa v 2.1-LCa v 2, in pMT2 plasmid, which bears an N-terminus from mammalian Ca v 2.1 (Spafford et al, 2003a;Spafford et al, 2004;Spafford et al, 2006). The wild-type channel was reconstructed with the Nterminus of wild-type LCa v 2 (GenBank Accession No.…”
Section: Materials and Methods Cloning Of Lca V 2 And Construction Ofmentioning
confidence: 99%
“…Shown in Fig.1A is a gene tree illustrating the relationships of human homologs to an identified set of calcium channel subunit genes from Lymnaea stagnalis, all previously expressed in human cell lines: LCa v 1 (Spafford et al, 2006), LCa v 2 (Spafford et al, 2003a) and LCa v 3 (Senatore and Spafford, 2010). Ca v 3 channels such as LCa v 3 bear transient, T-Type currents that are low voltageactivated (LVA) and open at resting membrane potentials (Senatore and Spafford, 2010).…”
Section: Introduction To the Lca V 2 Calcium Channelmentioning
confidence: 99%
“…2؉ oscillations required Ca 2؉ influx through VGCCs To determine whether CM-induced Ca 2ϩ oscillations involved Ca 2ϩ influx through VGCCs, the LPeD1 neurons were exposed to CM either in the presence of Ca 2ϩ channel blocker cadmium (Cd 2ϩ , 100 M) or nifedipine (10 M) shown previously to essentially block L-type Ca 2ϩ channels in Lymnaea neurons (Spafford et al, 2006). We found that CM-induced Ca 2ϩ increase in LPeD1 was gradually and completely blocked by Cd 2ϩ (n ϭ 8) (Fig.…”
Section: Cm-induced Camentioning
confidence: 99%